Enhanced upconversion luminescence induced by structrual evolution of lanthanum niobate phosphor. Issue 2 (March 2015) - Sun, Panpan; Dai, Pengpeng; Yang, Jikai; Zhao, Chengjiu; Zhang, Xintong
Abstract: A series of Yb 3+ -Er 3+ coactivated La(Nb 1-x V x )O4 (0≤ x ≤1) upconversion (UC) emission phosphors are prepared by high-temperature solid-state reaction method. Experimental results demonstrate that the introduction of V 5+ expands and distorts the unit cell volume of LaNbO4, and induces structural transformation of LaNbO4 from Phase 1 with monoclinic fergusonite structure (0< x ≤0.2) to Phase 2 with tetragonal scheelite structure (0.25≤ x ≤0.5) to Phase 3 with monoclinic monazite structure ( x =1). Under 976 nm excitation, continuously enhanced green UC emission is observed in Phase 1 with gradual replacement of Nb 5+ with the V 5+ (0< x ≤0.2). At x =0.2, the luminescence intensity is enhanced 1.3 times than that of the pristine sample. In Phase 2 and Phase 3, the intensity of green UC emission is decreased gradually with increasing the V 5+ concentration. Based on the XRD results and crystal structural analysis, the enhanced luminescence is attributed to the lowered symmetry around La 3+ ions (Er 3+ ions), which relaxes the parity-forbidden selection rules of Er 3+ luminescent centers. This study provides a useful approach in developing UC luminescence materials with controllable optical properties based on variations in local coordination environments through composition substitutions.